A qualitative application of temporal self-regulation theory to understand adherence to simple and complex medication regimens - Liddelow, Caitlin; Mullan, Barbara; Boyes, Mark; McBride, H. (MDPI, 2020)
Medication adherence is a global health concern, and variables of temporal self-regulation theory (TST) have been shown to be important in improving adherence. This qualitative study aims to explore how TST can help explain medication adherence in people’s daily lives, and whether there are differences in the adherence to simple and complex medication regimens. Twenty-nine participants from Australia engaged in semi-structured interviews based on TST (intention, behavioural prepotency, self-regulation), and other variables important to adherence. Interviews were analysed using thematic analysis. Six themes were identified (Routines, External Supports, Cost, Sense of Agency, Adverse Outcomes, and Weighing Up Pros and Cons), with partial support for TST (specifically intention, past behaviour, cues and planning). Four themes not related to TST were also identified. Individuals with more complex medication regimens spoke of the importance of routines, planning, and knowledge-seeking, whereas those with simpler regimens spoke of the importance of visual cues. TST may be useful for identifying some variables important in medication adherence, however, additional factors were also identified. For simple regimens, future research should focus on the manipulation of visual cues. For complex regimens, health professionals should consider supporting the use of medication management apps to assist in planning and ensuring a consistent routine.